2018
DOI: 10.1093/mnras/sty2452
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of dynamical phenomena in type II Cepheids of the OGLE collection

Abstract: We have analysed the photometry of 924 type II Cepheids from the Galactic bulge observed by the Optical Gravitational Lensing Experiment. Our goal was to detect and analyse various dynamical phenomena, including, e.g. multi-mode pulsation, perioddoubled pulsation, period-k pulsation, or quasi-periodic modulation of pulsation. First examples of double-mode BL Her-type stars, pulsating simultaneously in the fundamental and first overtone modes are reported. Two double-mode pulsators are not isolated cases howeve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Chaotic behavior was confirmed both from the ground (Buchler et al 1996;Kolláth et al 1998) and via Kepler data (Bódi et al 2016;Plachy et al 2018). Period doubling was also detected both with ground-and space-based observations in each subclass of Type II Cepheids Plachy et al 2017;Smolec et al 2018b;Jurkovic et al 2020). We note that light curves of Type II Cepheids can also be affected by extrinsic variations, usually connected to binarity.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Chaotic behavior was confirmed both from the ground (Buchler et al 1996;Kolláth et al 1998) and via Kepler data (Bódi et al 2016;Plachy et al 2018). Period doubling was also detected both with ground-and space-based observations in each subclass of Type II Cepheids Plachy et al 2017;Smolec et al 2018b;Jurkovic et al 2020). We note that light curves of Type II Cepheids can also be affected by extrinsic variations, usually connected to binarity.…”
Section: Introductionmentioning
confidence: 76%
“…The decade-long monitoring led to many discoveries, including low-amplitude additional modes and modulation (e.g. Moskalik et al 2006;Smolec et al 2018b;Süveges & Anderson 2018). Multi-epoch space photometry is also available for a large number of Cepheids with the Gaia Data Release 2 (DR2, Rimoldini et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For years, all type II Cepheids were considered to be pure fundamental-mode pulsators, until Smolec et al (2018) identified the first two cases of beat type II Cepheids in the OGLE Collection of Variable Stars (OCVS). Currently, a total of five objects belonging to this class are known in the Galaxy (Udalski et al 2018;Soszyński et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The first two double-mode type II Cepheids pulsating simultaneously in the fundamental and first-overtone modes were discovered by Smolec et al (2018), who identified them among nearly one thousand type II Cepheids detected by the OGLE survey in the Galactic bulge (Soszyński et al 2017b). These two unique objects have (fundamental-mode) periods equal to 1.04 d and 1.18 d, so they belong to the shortest-period subclass of type II Cepheids -BL Herculis stars -just above the conventional borderline (1 d) between RR Lyr stars and type II Cepheids.…”
Section: Introductionmentioning
confidence: 99%